A review of standards with cybersecurity requirements for smart grid. Issue 77 (August 2018) - Leszczyna, Rafał
Highlights: New, updated review of standards with cybersecurity requirements for smart grids that includes the newest standards' versions. High assurance of completeness due to the application of a repeatable and systematic literature search and analysis method. The details of the research method provided that include transparent standards' selection and evaluation criteria. 17 standards described from cyber security requirements perspective, and referred to the IEC smart grid architecture. The relationships between cybersecurity requirements in different standards analysed and visualised. Abstract: Assuring cybersecurity of the smart grid is indispensable for the reliable operation of this new form of the electricity network. Experts agree that standardised solutions and practices should be applied in the first place. In recent years many new standards for smart grids have been published, which paradoxically results in the difficulty of finding a relevant publication in this plethora of literature. This paper presents results of a study which aimed at addressing this issue by identifying all standards that define cybersecurity requirements applicable to smart grids. Based on a systematic literature review seventeen relevant standards were identified that are described in this paper with a focus on the requirements and characterised with respect to evaluation criteria. The relationships between the standards have been analysed to understand where the standards overlap or complement each other and where they are completely independent – as far as cybersecurity requirements are concerned. This together with the requirements-focused descriptions of the standards can serve as a useful guidance on cybersecurity requirements for smart grid components that should help practitioners in choosing the standards that are applicable to their area or a specific problem.